Preparation and characterization of oil palm fiber-reinforced PCL composites for reduction of electromagnetic interference - Ibrahim, Radzi Rahman (2017)
Microwave absorbers are used in a wide range of applications to eliminate stray or unwanted radiation that could interfere with a system’s operation. For example, the Wireless Avionics Intra-Communications protocol imposed only a minimum shielding effectiveness of only 5dB for the aircraft structural design. It generally consist of a filler material inside a material matrix. The filler consists of one or more type of material that do most of the absorbing. The matrix material is chosen for its physical properties (temperature resistance, weather ability, etc.). This thesis presents the development of a natural oil palm empty fruit bunch fiber (OPEFB)-reinforced polycaprocalctone (PCL) composites with Iron Oxide (Fe2O3) for microwave shielding and absorbing applications. Oil palm empty fruit bunch fiber exhibit excellent mechanical properties when compared with other natural fibers. The OPEFB and PCL are biodegradable, cheap and less dangerous compared to industrial materials. The fillers which is OPEFB and Fe2O3 were prepared by the conventional solid-state method. Different compositions of filler were doped and blended to produce OPEFBPCL and OPEFB-PCL- Fe2O3 composites. The crystalline structure of the composites was analyzed using X-ray diffraction (XRD) machine to ensure the sample only containing the fillers without any contamination while the theoretical calculation of the transmission coefficients of the sample placed in the waveguide was computed using Finite Element Method (FEM) and was accomplished using COMSOL software. The transmission and reflection coefficients as well as dielectric properties were measured using a PNA (N5227) Network Analyzer from 8 GHz to 12 GHz at room temperature by using open ended coaxial (OEC) and rectangular waveguide (RWG) technique. The permittivity of the composites was found to be dependable on the mixing ratio values between OPEFB, PCL, and Fe2O3. Both the dielectric constant and loss factor of the OPEFB-PCL and OPEFB-PCL-Fe2O3 composite increased with increasing percentages of OPEFB and Fe2O3 .fillers respectively. The dielectric constants of OPEFB-PCL composites were found to between 2.50 and 3.44 with similar loss factor from 0.17 to 0.40 in the X-band frequency. Furthermore the dielectric constant of OPEFB-PCL-Fe2O3 composites were found to be between 3.17 to 3.50 and similar loss factor from 0.25 to 0.40 respectively in the X-band frequency. These, in turn, will lead to higher values of the magnitude reflection coefficient |S11| and lower transmission coefficient |S21| by the impedance matching theory. OPEFBPCL composites with Fe2O3 fillers provide cost-effective solutions for shielding effectiveness.